Education, Attitudes, and Motivation of Entrepreneurship: Study of Knowledge Transfer at Small Business in Makassar City - Sitti Hajerah Hasyim; Muhammad Hasan; Tuti Supatminingsih; Muhammad Imam Ma’ruf; Nuraisyiah Nuraisyiah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to review the direct and indirect effect of entrepreneurship education in family towards attitudes of entrepreneurship and to explain the direct and indirect effect of entrepreneurship education in family and also attitudes of entrepreneurship toward entrepreneurship motivation for the young generation on small scale family businesses in Makassar city. This research is explanatory research. There are 1.267 small scale family businesses as the population, while only 130 small scale family businesses as the sample in this research, in considerate the businesses have been running for at least 2 generations. The result of this research showed that entrepreneurship education has significant effect toward attitudes of entrepreneurship and attitudes of entrepreneurship has significant effect toward entrepreneurship motivation. Based on path analysis, the result showed entrepreneurship education has significant effect toward entrepreneurship motivation through mediating of attitudes of entrepreneurship